Does a patient’s physical activity predict recovery from an episode of acute low back pain?: a prospective cohort study - Hendrick, Paul; Milosavljevic, Stephan; Hale, Leigh; Hurley, Deirdre A.; McDonough, Suzanne M.; Herbison, Peter; Baxter, G. David (BioMed Central, 2013)
Background Advice to remain active and normalisation of activity are commonly prescribed in the management of low back pain (LBP). However, no research has assessed whether objective measurements of physical activity predict outcome and recovery in acute low back pain.